GROWTH AND YIELD OF SOME LENTIL ( Lens culinaris Medic ) GENO TYPES AS AFFECTED BY POTASSIUM FERTILIZER - A.M. Al-Hasan (Mesopotamia Journal of Agriculture)
A field experiment was conducted during the growing season 1999-2000 two different location in north Iraq viz ; Sallameah ( 40 km south of Mosul ) , and Rabiah ( 92 km north-west Mosul ) to study the effect of two level of potassium fertilizer, and kgK2O/ha , on growth and yield of sixteen genotype of lentil .The experiment was carried out using split-plot in R.C.B.D. with three replacements . Fertilization with 40 km K2O/ha increased significantly pod number/plant ,seed and biological yield at Salllameah location , number of primary and secondary branches/plant and seed yield at Rabiah location .Genotype differed significantly for all studies characters at both location except for the number of secondary branches/plant at Sallameah location . The genotype F96-25L was the earliest in maturity at both location , while the local variation were the latest in maturity . Genotype 78S 26002 was superior to local variation and most other genotypes in pods/plant and seed yield at Rabeah location while genotype F96-25L was superior to local variation and most other introduce genotype in pods/plant , yield and biological yield at Sallameah location .